The effect of the operability of the support roller on the deformation of the printing cylinder from the action of the gripping system - Serkova L.B.; Varepo L.G. (Научно-технический вестник Брянского государственного университета)
Of particular importance to the combination of inks and the accuracy of sheet transmission in the sections of the printing press is the sheet transmission system, the malfunction of which leads to defective products or machine failure. This problem is often associated with the appearance of additional movements in the support roller of the cam mechanism of the leaf transfer system, which leads to displacement of the gripping system, its distortion or complete failure. The paper considers the results of studying the deformation abilities of a printing cylinder from the action of a locking system. Various cases of load action are considered: the system operates evenly along the length of the cylinder, as well as with an offset on one side. To conduct a virtual experiment, a three-dimensional model of a printed cylinder has been developed, which has a technological recess for placing technological equipment in it, namely, a gripping system for a sheet-transmitting system. The virtual experiment was performed using the finite element method. It is determined that in case of malfunction of the support roller of the printing system, the displacement of the largest deformations towards one of the supports of the printing cylinder is observed. It is noted that the displacement of the gripper system along the length of the cylinder equal to 1 mm doubles the deformation of the cylinder.